2023
DOI: 10.3389/fcimb.2023.1125640
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the microbiota composition in the genital tract of infertile patients with chronic endometritis or endometrial polyps

Abstract: BackgroundThe previous researches show that infertile patients have a higher incidence of endometritis and endometrial polyps, and the occurrence of these two diseases is related to changes in the microbiota of the genital tract. We aim to determine the composition and changing characteristics of the microbiota in the genital tract (especially the endometrium) of infertile patients with chronic endometritis or endometrial polyps, and find the correlation between it and the occurrence of diseases.MethodsThis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Recent research is uncovering a link between infertility and the mix of microbes in the reproductive system [ 14 18 ]. Studies have found that infertile women tend to have more asymptomatic vaginal infections [ 15 ] and a different mix of uterine bacteria [ 16 ], including those often linked to conditions like bacterial vaginosis, chronic endometritis, and endometrial polyps [ 16 ]. Fertility dysfunction may be associated with the degradation of immune tolerance due to decreased Treg cells’ function and quantity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research is uncovering a link between infertility and the mix of microbes in the reproductive system [ 14 18 ]. Studies have found that infertile women tend to have more asymptomatic vaginal infections [ 15 ] and a different mix of uterine bacteria [ 16 ], including those often linked to conditions like bacterial vaginosis, chronic endometritis, and endometrial polyps [ 16 ]. Fertility dysfunction may be associated with the degradation of immune tolerance due to decreased Treg cells’ function and quantity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Liang et al. found no significant differences in alpha and beta diversities between the two groups ( Liang et al., 2023 ). The disparities in these results could be attributed to variations in the selection of the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have extensively explored alterations in the uterine cavity microbiota of patients with EPs, including an elevated proportion of Firmicutes and a decreased proportion of Proteobacteria at the phylum level. Furthermore, enrichment of specific genera such as Lactobacillus , Staphylococcus , Bifidobacterium , Gardnerella , and Bacteroides was observed, along with a decreased level of Pseudomonas at genus levels ( Fang et al., 2016 ; Horban et al., 2019 ; Liang et al., 2023 ). Our study aligns with these previous findings and confirms significant abundance changes in the endometrial microbiota of patients with EPs, particularly in relation to Proteobacteria , Bifidobacterium , Staphylococcus , and Pseudomonas .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations